صورة المرأة في الإشهار التلفزيوني دراسة سيميولوجية للومضات الإشهارية في الفضائيات الجزائرية - مراد أحلام (My University, 2019)
Summary of the study: Television advertising is currently used to sell and promote an advertising product, but it can create a range of perceptions, concepts and values that affect the public by relying on the image of the woman for the provision of various goods and services. services. We therefore conducted a semiological study on a sample of advertising flashes in Algerian satellite channels, in order to identify the image of women in television advertising broadcast on Algerian satellite channels. To achieve this goal, we adopted the descriptive approach and the semiological analysis tool for three advertising flashes using the Roland Barth approach, a descriptive reading, then the reading of the appointment and the implicit reading to answer the questions of the study and lead to a set of results of the analysis, which are the most important: • The study showed that these flashes had aesthetic and artistic dimensions: the aesthetics of lighting and colors and their varied artistic uses, as well as the aesthetics of characters and editing, also focused on the aesthetics of the woman mixing feminine beauty and natural beauty. • The study found that the congruence between linguistic and iconic in advertising flash is a deliberate process to produce implicit meanings that the recipient understands after interpreting visual connotations. • The study also revealed that television programs contributed to distort the image of Algerian women, which appears artificially contrary to the Islamic religion and incompatible with customs and traditions. • In addition, this study also revealed that women play an important role in influencing the public. ------------------------ ملخص الدراسة: يُستخدم الإعلان التلفزيوني حاليًا لبيع وترويج منتج إعلاني، إلا أنه قد يُنشئ مجموعة من التصورات والمفاهيم والقيم التي تؤثر على الجمهور من خلال اعتماده على صورة المرأة في تقديم مختلف السلع والخدمات. لذلك، أجرينا دراسة سيميائية على عينة من الومضات الإعلانية في القنوات الفضائية الجزائرية، بهدف تحديد صورة المرأة في الإعلانات التلفزيونية التي تُبث على القنوات الفضائية الجزائرية. ولتحقيق هذا الهدف، اعتمدنا المنهج الوصفي وأداة التحليل السيميائي لثلاث ومضات إعلانية، مستخدمين منهج رولان بارث، قراءة وصفية، ثم قراءة الموعد، والقراءة الضمنية، للإجابة على أسئلة الدراسة، والتوصل إلى مجموعة من نتائج التحليل، أهمها: • أظهرت الدراسة أن لهذه الومضات أبعادًا جمالية وفنية، تتمثل في جماليات الإضاءة والألوان واستخداماتها الفنية المتنوعة، وجماليات الشخصيات والمونتاج، كما ركزت على جماليات المرأة التي تمزج بين الجمال الأنثوي والجمال الطبيعي. • توصلت الدراسة إلى أن التطابق اللغوي والأيقوني في الومضات الإعلانية هو عملية مقصودة لإنتاج معانٍ ضمنية يفهمها المتلقي بعد تفسير الدلالات البصرية. • كشفت الدراسة أيضًا أن البرامج التلفزيونية ساهمت في تشويه صورة المرأة الجزائرية، مما يظهرها بصورة مصطنعة ومخالفة للدين الإسلامي، ومخالفة للعادات والتقاليد. • بالإضافة إلى ذلك، كشفت هذه الدراسة أيضًا أن المرأة تلعب دورًا مهمًا في التأثير على الجمهور.
Keywords: صورة المرأة، الإشهار التلفزيوني، ومضات الإشهارية، الفضائيات الجزائرية